Cu/CuxOy NPs architectured COF: a recyclable catalyst for the synthesis of oxazolidinedione via atmospheric cyclizative CO2 utilization. Issue 81 (14th September 2020) - Sarkar, Somnath; Ghosh, Swarbhanu; Mondal, Jahangir; Islam, Sk. Manirul
Abstract : This work emphasizes the utility of COFs in establishing a heterogeneous catalytic system for the generation of value-added oxazolidinediones under alkali-free conditions (sustainable approach). Abstract : The present study describes the favourable construction of a crystalline covalent organic framework (COF) with exceptional surface area, tunable pore size and huge CO2 capture efficiency to facilitate a novel multicomponent cyclization by introducing CO2 into extremely reactive organic skeletons. In the presence of a catalytic Cu/Cu x O y NP-loaded COF, several 2-bromo-3-alkylacrylic acids combined with several amine derivatives and CO2 (0.1 MPa) are converted to the desired oxazolidinediones in excellent yields (up to 96%) under alkali-free conditions and ambient temperature.